Mesenchymal stromal cells-derived exosome and the roles in the treatment of traumatic brain injury - Mot, Yee Yik; Moses, Emmanuel Jairaj; Mohd Yusoff, Narazah; Ling, King Hwa; Yong, Yoke Keong; Tan, Jun Jie (Springer New York, 2022)
Traumatic brain injury (TBI) could result in life-long disabilities and death. Though the mechanical insult causes primary injury, the secondary injury due to dysregulated responses following neuronal apoptosis and inflammation is often the cause for more detrimental consequences. Mesenchymal stromal cell (MSC) has been extensively investigated as the emerging therapeutic for TBI, and the functional properties are chiefly attributed to their secretome, especially the exosomes. Delivering these nanosize exosomes have shown to ameliorate post-traumatic injury and restore brain functions. Recent technology advances also allow engineering MSC-derived exosomes to carry specific biomolecules of interest to augment their therapeutic outcome. In this review, we discuss the pathophysiology of TBI and summarize the recent progress in the applications of MSCs-derived exosomes, the roles and the signalling mechanisms underlying the protective effects in the treatment of the TBI.